An unusual localization of echinococcosis: Gallbladder hydatid cyst. (2022) - Kbir, Ghassen Hamdi; Messaoudi, Sohaib; Selmi, Marwen; Maatouk, Mohamed; Bouzidi, Mohamed Tahar; Ennaceur, Farouk; Ben Moussa, Mounir
Abstract: Echinococcosis is endemic in Mediterranean countries. Liver then lungs are the most affected organs. Gallbladder hydatid cyst is an exceptional localization. A 64-year-old patient was referred to our surgical outpatient department by his physician for suspicion of liver hydatid cyst based on right upper quadrant abdominal pain, associated with nausea. Physical examination showed mild tenderness of the right upper quadrant of the abdomen. A computed tomography abdominal scan showed a multivesicular cystic lesion of the segment IV measuring 9.5 × 7.5 × 13 cm with exophytic component abutting the gallbladder. The patient underwent right subcostal laparotomy. The exploration has found that the hydatid cyst is developed from the fundus of the gallbladder, without any connections or fistulas to nearby organs. A cholecystectomy was performed. Histopathological examination confirmed the diagnosis of gallbladder echinococcosis. Primary gallbladder hydatid cysts (PGHC) is an extremely rare condition, occurring in less than 0.4% of echinococcosis localizations. After literature research of case reports, only twenty-three such cases, including our case, have been reported in English literature. Due to its uncommon nature, radiologists rarely consider a PHGB as the first diagnosis. Preoperative diagnosis of hydatid cyst was possible only in 50% of cases. Therefore, a careful attention is necessary to assist in making the diagnosis preoperatively, leading to the appropriate treatment.